2017
DOI: 10.1073/pnas.1714616114
|View full text |Cite
|
Sign up to set email alerts
|

College completion predicts lower depression but higher metabolic syndrome among disadvantaged minorities in young adulthood

Abstract: SignificanceCollege graduates enjoy healthier, longer lives compared with individuals who do not graduate from college. However, the health benefit of educational attainment is not as great for blacks as it is for whites. Moreover, college completion may not erase the detrimental effects of early-life disadvantage for blacks and Hispanics. We use nationally representative data on young adults to test whether American minorities experience differential returns to educational attainment. We find that college com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 58 publications
12
76
6
Order By: Relevance
“…The exact biological mechanism linking compulsory schooling to poorer health remains unclear and should be the subject of future research. Our findings relate to research in the United States showing that disadvantaged minorities with higher education reported higher allostatic load and cardiovascular biomarkers than their less educated counterparts (Brody et al, 2013;Gaydosh, Schorpp, Chen, Miller, & Mullan Harris, 2018;Miller, Yu, Chen, & Brody, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…The exact biological mechanism linking compulsory schooling to poorer health remains unclear and should be the subject of future research. Our findings relate to research in the United States showing that disadvantaged minorities with higher education reported higher allostatic load and cardiovascular biomarkers than their less educated counterparts (Brody et al, 2013;Gaydosh, Schorpp, Chen, Miller, & Mullan Harris, 2018;Miller, Yu, Chen, & Brody, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, in the National Longitudinal Study of Adolescent to Adult Health, lower levels of depression are associated with college completion, irrespective of childhood disadvantage and for all racial/ethnic groups (blacks, whites, Hispanics) (Gaydosh et al 2018). In contrast, college completion is associated with lower metabolic syndrome for whites, irrespective of exposure to childhood disadvantage, but among black and Hispanic youth, college completion is associated with higher metabolic syndrome among those from disadvantaged childhood environments.…”
Section: Other Key Priorities For Future Researchmentioning
confidence: 99%
“…"Exception" cases are often used to justify the existence of an unrealistic working meritocratic system of equal opportunity and place the onus of academic achievement entirely upon the individual (Henry, 2015;McWhorter, 2000;Tough, 2013). However, this research complicates those theories and validates evidence that even the most accomplished strivers might deal with severe physiological ailments which may in fact be preventable (Gaydosh et al, 2017).…”
Section: Discussionmentioning
confidence: 52%
“…Finally, it is important to understand that from a wellness perspective, college completion and professional success should not necessarily be in and of itself a metric of accomplishment and fulfillment. On the contrary, it has been found that the college completion of low-income racial minority students is associated with greater stress over the life course, perhaps from pressure to perform and resulting overwork (Gaydosh et al, 2017). This is a bleak reality and an understudied health cost to social mobility.…”
Section: Significance and Implicationsmentioning
confidence: 99%